Raw Milk Microbiota Modifications as Affected by Chlorine Usage for Cleaning Procedures: The Trentingrana PDO Case - Cremonesi, Paola; Morandi, Stefano; Ceccarani, Camilla; Battelli, Giovanna; Castiglioni, Bianca; Cologna, Nicola; Goss, Andrea; Severgnini, Marco; Mazzucchi, Massimiliano; Partel, Erika; Tamburini, Alberto; Zanini, Lucio; et al. (Frontiers in Microbiology, 2020)
Milk microbiota represents a key point in raw milk cheese production and contributes to the development of typical flavor and texture for each type of cheese. The aim of the present study was to evaluate the influence of chlorine products usage for cleaning and sanitizing the milking equipment on i) raw milk microbiota; ii) the deriving whey-starter microbiota; and iii) Trentingrana PDO cheese microbiota and volatilome. Milk samples from three farms affiliated to a Trentingrana PDO cheese factory were collected three times per week during a six-weeks period in which a sodium hypoclorite detergent (period C) was used and during a subsequent six-weeks period of non-chlorine detergent usage (period NC). Samples were subjected to microbiological (Standard Plate Count; coliforms; staphylococci coagulase positive; and lactic acid bacteria and metagenomic analysis (amplification of V3-V4 regions of 16S rRNA gene performed on Illumina MiSeq platform). In addition, cheese volatilome was determined by SPME-GC-MS. In the transition from period C to period NC, higher SPC and lactic acid bacteria counts in milk were recorded. Milk metagenomic analysis showed a peculiar distinctive microbiota composition for the three farms during the whole experimental period. Moreover, differences were highlighted comparing C and NC periods in each farm. A difference in microbial population related to chlorine usage in bulk milk and vat samples was evidenced. Moreover, chlorine utilization at farm level was found to affect the whey-starter population: the usually-predominant Lactobacillus helveticus was significantly reduced during NC period, whereas L. delbrueckii had the exact opposite trend. Alpha- and beta-diversity revealed a separation between the two treatment periods with a higher presence of L. helveticus, L. delbrueckii and S. thermophilus in cheese samples after NC detergent period. Cheese volatilome analysis showed a slight decrease in lipolysis during C period in the inner part of the cheese wheel. Although preliminary, these results suggest a profound influence on milk and cheese microbiota, as well as on raw milk cheese production and quality, due to the detergent type used. However, further studies will be needed to better understand the complex relationship between detergent and microbiota along all the cheese production steps.